Mechanisms of Primary and Secondary Resistance to Immune Checkpoint Inhibitors in Cancer - Tiffany Seto (Medical Sciences, 2019)
Immune checkpoint inhibitors (ICPis) have revolutionized cancer therapy with broad activities against a wide range of malignancies. However, in many malignancies their efficacy remains limited due to the primary resistance. Furthermore, a high percentage of patients develop progression due to the secondary resistance even after obtaining a response or achieving a stable disease. In this review, we will discuss the mechanisms that underlie the primary and secondary resistance to ICPis in cancer immunotherapy and provide an overview to impart a broad understanding of the critical issues that are encountered in clinical oncology practice.